2006
DOI: 10.1016/j.jcrs.2006.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Brinzolamide 1% versus apraclonidine 0.5% to prevent intraocular pressure elevation after neodymium:YAG laser posterior capsulotomy

Abstract: Brinzolamide 1% and apraclonidine 0.5% given prophylactically before Nd:YAG laser capsulotomy were effective in preventing IOP spikes after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Barnes et al 2 reported a 2% rate among 47 patients treated with either acetazolamide or apracloni-dine. Unal et al 11 examined 115 patients and reported a stable IOP following apraclonidine and capsulotomy (from 16.1 to 15 mm Hg) and a relatively high rate of IOP spikes > 5 mm Hg seen in 8.6% (5/58) of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnes et al 2 reported a 2% rate among 47 patients treated with either acetazolamide or apracloni-dine. Unal et al 11 examined 115 patients and reported a stable IOP following apraclonidine and capsulotomy (from 16.1 to 15 mm Hg) and a relatively high rate of IOP spikes > 5 mm Hg seen in 8.6% (5/58) of their patients.…”
Section: Discussionmentioning
confidence: 99%
“… 8 13 Reported rates of IOP spikes above 5 mm Hg following prophylactic apraclonidine 0.5% and capsulotomy vary between 2 and 8.5%. 2 5 11 12 …”
Section: Introductionmentioning
confidence: 99%
“…Em concordância com a literatura (7,(16)(17)24) , constatou-se que houve um aumento significante da PIO nas primeiras duas horas e após esse período, a PIO retornou a valores iniciais. Após 2 horas, é raro haver picos hipertensivos após capsulotomia.…”
Section: Discussionunclassified
“…Estudos recentes apontam que o material e desenho das lentes intra-oculares de polimetilmetacrilato (PMMA) induzem mais à opacificação que as lentes de acrílico hidrófobo e lentes implantadas no sulco induzem a uma hipertensão maior que se fossem implantadas no saco capsular (12) . O controle da PIO tem sido feito por alguns agentes hipotensores oculares como bloqueadores adrenérgicos: maleato de timolol (3) e levobunolol (14) , parassimpáticomimético: pilocarpina (15) , inibidores da anidrase carbônica: acetazolamida sistêmica (16) e dorzolamida tópico (17)(18) , derivado da prostaglandina: latanoprosta (19) , agonistas adrenérgicos seletivos: apraclonidina (20) , brimonidina (21)(22)(23) e brinzolamida (24) . As possíveis vantagens e desvantagens dos diversos hipotensores disponíveis ainda não foram pesquisadas em uma única série.…”
Section: Resumo Introduçãounclassified
“…Teresa, Nancy and Unal in their study, showed that the use of brimonidine 0.15% before surgery is comparable to the efficacy and safeness of apraclonidine 0.5% and 0.1% in preventing IOP elevation after laser anterior segment capsulotomy. 5,6,16 Seong et al in a study identified the positive influence of brimonidine 0.2% as an eye drop in preventing IOP elevation after YAG laser capsulotomy. 7 Yeom and et al in a study used two different concentrations of brimonidine (0.2% and 0.15%) and showed their high effectiveness in preventing IOP rise after YAG laser capsulotomy and also they suggest that both drugs had a similar impact on preventing IOP increase.…”
Section: Xalatan Brimonidinementioning
confidence: 99%